Farmers' producer organisation in reducing transactional costs: A study of Tamil Nadu Mango Growers Federation (TAMAFED) - R, SAKTHI PARTHIBAN; NAIN, M S; SINGH, RASHMI; KUMAR, SHIV; CHAHAL, V P (The Indian Journal of Agricultural Sciences, 2015)
The functional linkages of producers with different systems and within the system in the form of backward and forward linkages in production process involve the investments in the form of transactional costs. Farmers’ collective action for better production in the form of self help groups (SHGs), farmers’ interest groups (FIGs), marketing associations, producers associations, co-operatives etc. have contributed in maximizing the input-output ratio and ultimately increasing the benefit of producers. The present study was undertaken to find out the motivating factors to join association and the benefits accrued as a result of joining such producers’ federation namely TAMAFED (Tamil Nadu Mango Growers Federation) dealing with mango crop in Tamil Nadu state of India. A set of sixty member and sixty non-member farmers were selected from the six villages of the three districts of the state. The Logit analysis revealed that education, economic benefit and area under mango cultivation were the major determinants of motivation to join TAMAFED. As a measure of economic gain, transactional output cost due to sale of harvested produce was two and half times less for members compared to non-members. The comparative analysis shows that mean transactional input cost per hectare was found to be significantly lower for members than non-members. The members of TAMAFED gained social and economic benefits and the costs incurred on input and output transactions were quite low ultimately adding to the benefit. As such, it may be recommended that organization of farmers on commodity basis in the form of similar federations may be promoted for socio economic gain of the farmers.